Towards peace and reconciliation after the Great War: Letter-writing to the League of Nations - Bouchard, Carl (Peacebuilding, Memory and Reconciliation. Bridging Top-Down and Bottom-Up Approaches, 2011)
Towards peace and reconciliation after the Great War - 1 - Letter-writing to the League of Nations